Characterization of rhizosphere colonization by luminescent Enterobacter cloacae at the population and single-cell levels. - Rattray, E A (1995)
A bioluminescence marker system was used to characterized colonization of the rhizosphere by a bacterial inoculum, both in terms of population activity and at the single-cell level. Plasmid pQF70/44, which contains luxAB genes under the control of a strong constitutive phage promoter, was introduced into the rhizobacterium and model biocontrol agent Enterobacter cloacae. Light output from the lux-modified strain was detected by luminometry of samples from growing cultures of E. cloacae and from inoculated soil and wheat root samples. The minimum detection limits for fully active cells under optimum conditions were 90 and 445 cells g-1 for liquid culture and soil, respectively. The metabolic activities of the lux-marked population of E. cloacae, characterized by luminometry, contrasted in rhizosphere and nonrhizosphere soil. Cells in the rhizosphere were active, and there was a linear relationship between light output and cell concentration. The activity of cells in nonrhizosphere coil could not be detected unless the soil was supplied with substrate. Novel use of a charge-coupled device is reported for the spatial characterization of rhizosphere colonization by E. cloacae (pQF70/44) at the single-cell and population levels. Used macroscopically, the charge-coupled device identified differences in colonization due to competition from indigenous soil organisms. The lux-marked bacterium was able to colonize all depths of roots in the absence of competition but was restricted tot he spermosphere in the presence of competition (nonsterile soil).(ABSTRACT TRUNCATED AT 250 WORDS)